A Comparison of the Macroeconomic Effects of Increased Defence Spending in Poland and Germany - Krajewski, Piotr; Piłat, Katarzyna (Comparative Economic Research. Central and Eastern Europe, 2023)
The aim of the article is to quantify and compare the macroeconomic effects of defence spending in the Polish and German economies. Estimating these effects is of particular importance in the context of the substantial increase in defence expenditures in Poland and Germany resulting from the war in Ukraine. The research is based on a dynamic stochastic general equilibrium model that takes into account both demand‑side and supply‑side mechanisms. The impulse response functions calculated based on the models estimated for the two economies show that the impact of defence spending on GDP is much stronger in Poland than in Germany. Furthermore, the empirical results indicate that in the Polish economy, defence spending also stimulates labour and consumption to a greater extent than in the German economy.